Analisis Implementasi Manajemen Operasional PT. Tom Burger Group di Kab. Lima Puluh Kota - Stefanny Angelina Firdaus; Novera Martilova (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
In today's era, the food industry has grown very rapidly, especially with the increasing demand for quality and innovative food. The rapidly growing industry today makes competition between companies in the world increasingly tight. Each company will compete to be at the forefront to meet consumer needs in the market in order to survive in the midst of competition. Every company or industry must have a vision and mission to continue to grow in addition to obtaining great profits. PT. TOM BURGER GROUP is one of the famous food industry companies in West Sumatra. The type of research used in this study is qualitative research with a descriptive approach. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The results of this study indicate that PT. TOM BURGER GROUP has carried out operational management well, but behind that there are still obstacles faced by the company in carrying out its operational management, but with the solutions implemented by PT. TOM BURGER GROUP can be expected that the company's operations will run well. The implementation of operational management has indeed been carried out at PT. Tom Burger Group by planning the production system, controlling production and implementing a production information system.